THE USE OF NON-VERBAL LANGUAGE IN HOTEL ADVERTISEMENTS: SEMIOTIC ANALYSIS - Agustia, Km Tri Sutrisna; Dewi, Putu Chrisma; Kurniawan, Ida Bagus (Annual International Conferences on Language, Literature, and Media, 2023)
The purpose of non-verbal language in a digital advertisement is to supplement the advertisement's information delivery. This study examines the meaning of the non-verbal language used in hotel advertisements in Bali taken from their official channel in YouTube, as well as to determine if the non-verbal language is adequate to convey the advertisements' messages. It employed a qualitative approach to acquire data from research participants through digital advertisements for marketing devices collected from digital social media as visual media. The analysis concerned the nonverbal actions in digital advertisements, including facial expressions, gestures, body language, movement, contact, and appearance. Two advertisements on the Official YouTube channel of Hilton Nusa Dua and Indigo Seminyak provide the source of the data. The advertisements were observed and chosen based on their nonverbal content. Nonverbal language's significance in the two advertisements analyzed in this study cannot exist alone. Aspects of the use of nonverbal language in the two advertisements have varying connotations and miss the mark due to the absence of verbal language. Bali identification and tourism quality, such as culture, environment, and art, were not communicated. Because there is no verbal component, there still needs to be a misinterpretation of the meaning of nonverbal language in the two advertisements discussed. The advertisements can be understood based on semiotic principles, but they must be supplemented with verbal language to prevent misunderstandings regarding the advertisements.